DAMPAK PEMASARAN TERHADAP JASA ANGKUTAN BARANG DENGAN STUDI KASUS PT. JASA PRIMA LOGISTIK BULOG - Suroyo Suroyo; Aprianto Miduk Pandapotan Saragih; Parlin Sinaga (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
One of the business fields run by the company is engaged in the service business. Both in the form of transportation services, tours and travels, health services, lodging services, laundry services, and freight forwarding services. In general, the delivery of these goods uses air transportation because airplanes are still the fastest means of transportation at this timeThe data collection techniques that the author uses in writing this scientific work are Interview and Questionnaire. After the relevant data is collected, then the data is processed. In preparing the discussion of this research report, the author uses descriptive data analysis. Descriptive approach is to collect, classify and compile existing data then analyze the data and then relate it to theories related to the problem From the responses of the respondents it can be concluded that from 100 respondents more said that the satisfaction of the services provided by PT. Bulog's Prima Logistics Service is Agree, which is 45 people. Although 10 people answered Don''t Agree, 45 people who answered Agree have proven that the services provided by the company are right for consumers. From the results of research and analysis conducted on the variables causing the non-fulfillment of the delivery of goods at PT. Excellent Logistics Service. Then, several dominant variables that cause the delivery target not to be achieved can be stated as Product, Promotion, people, Process, and Customer Service